Analysis of Process Variables Effect on The Efficiency of Soxhletation Extraction of Larvae Oil (Hermetica illucens) using Response Surface Methodology - Fitria, Murni; Rhea Alvita, Livia; Ariski Putra, Feby; Variyana, Yeni; Hanifah, Windia (Indonesian Journal of Chemical Analysis (IJCA), 2025)
Maggot or Black Soldier Fly (BSF) larvae can be used as a source of oil because they have a high lipid content. In this study, the maggot oil extraction process was optimised using the soxhlet method with the assistance of the response surface methodology (RSM) using the Central Composite Design (CCD) research design. Optimization was carried out with variations in the ratio: solvent (1: 7, 1: 10 and 1: 13 g/mL) and extraction time (120, 240 and 360 minutes). The results of the significance test using ANOVA showed that the sample solvent comparison had an insignificant effect (p-value: 0.060). In contrast, the extraction time had a significant effect (p-value: 0.000) on the maggot oil harvest yield. The results of different analyses showed a significant quadratic interaction between the sample solvent comparison (p-value: 0.002) and a significant interaction between the sample solvent comparison and extraction time (p-value: 0.008). The recommended optimal conditions based on optimization using RSM are a combination of a sample solvent ratio of 1:8.5 and an extraction time of 360 minutes with a predicted oil yield of 32.11%. Meanwhile, experimental validation at the recommended optimal conditions produced a yield of 38.68% or greater than the predicted value. The characteristics of the maggot oil obtained had a density of 0.9493 g/mL, a viscosity of 0.92 Pa.s, an air content of 0.0847% w/w, and free fatty acids of 4.56%. The results of GC-MS analysis of maggot oil showed a total of 9 compounds, with the 3 most abundant compounds being oleic acid (52.6%), palmitic acid (24.78%), and lauric acid (12.45%).